An exploration of futility and extreme risk in emergency laparotomy - Javanmard-Emamghissi, Hannah (2024)
An emergency laparotomy is an invasive abdominal surgical procedure used to treat conditions such as intestinal perforation or obstruction. It is one of the most common emergency surgeries worldwide, but is associated with significant mortality and morbidity. The National Emergency Laparotomy Audit (NELA) was established in 2012 to improve outcomes for emergency laparotomy patients in England and Wales. Prior to NELA’s establishment the national outcomes of these patients were completely unknown. NELA’s work identified groups of patients that had worse outcomes than their peers or were undefined and understudied; in particular older patients, very high-risk patients and those that died in the early post-operative period. The aim of the thesis was to address these areas of research paucity.